2010
DOI: 10.4103/0970-0218.66892
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of malnutrition among adolescents: Can BMI be replaced by MUAC

Abstract: Objectives:To find out the magnitude of malnutrition among the adolescents of an urban slum of Kolkata study population. To compare the middle upper arm circumference (MUAC) with that of body mass index (BMI) for determination of nutritional status of the study population.Materials and Methods:This was a school-based descriptive epidemiological study done among adolescent male students aged 10–19 years in the service area of Urban Health Centre, Chetla. The school is an all boy’s government aided school and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 4 publications
6
44
0
Order By: Relevance
“…1 Adolescence is a period, which forms the base of future health and social life. The health problems and habits acquired during this phase prove a lifelong hindrance in well-being.…”
Section: Introductionmentioning
confidence: 99%
“…1 Adolescence is a period, which forms the base of future health and social life. The health problems and habits acquired during this phase prove a lifelong hindrance in well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in similar settings have also shown that use of MUAC has improved the ability of front-line health workers to screen and assess for acute malnutrition among children for community-based management of acute malnutrition services 2-4 . Studies comparing diagnostic accuracy established that MUAC correlates well with BMI in adult populations [5][6][7][8][9][10] .…”
Section: Dear Editormentioning
confidence: 99%
“…Waist circumference acts as a better indicator of visceral adiposity. 4,5 Recent studies have reported a relationship between waist circumference and BMI. 6 Another anthropometric parameter, which has gained attention recently, is waist-to-height ratio (WHtR).…”
Section: Introductionmentioning
confidence: 99%